The use of numerical modelling to assess soil water dynamics in subsurface irrigation - Oliveira Rocha, Mayara (2023)
Knowledge of soil water dynamics is essential for establishing appropriate methods of irrigation management. Waterdynamics in unsaturated soils is a complex process that can be explained by the Richards equation. As this is a non-linear differentialequation, there is no analytical solution, but requires the use of the fi nite element method, for example, to obtain solutions, wheresimulations using numerical modelling make it p ossible to predict the the fl ow of water from the soil. As such, the aim of this studywas to evaluate a 2D numerical model in simulating wate r distribution and wet bulb formation resulting from a subsurface irrigationsystem, in addition to validating the generated model. The Pearson correlation coeffi cient (r), the coeffi cient of deter mination (R2) andthe root-mean-square error (RMSE) were calculated. For each treatment, both during and after irrigation, the model showed a smallrelative error, high values for R2and a positive correlation with the fi eld data. It was concluded that the model is applicable to the designand management of subsurface irrigation systems, varying the installation depth of the drip tube, the spacing between emitters and thesoil moisture, giving good results for the various simulated scenarios.